Transmission Congestion Management in Deregulated Electricity Market using Multi-Objective Grasshopper Optimization Algorithm - Chatuanramtharnghaka, Benjamin; Deb, Subhasish (EAI Endorsed Transactions on Energy Web, 2020)
In this paper, a study of multi-objective based congestion management is carried out by generator rescheduling with considering generator fuels cost. Due to the rapid growth of electrical load, the pressure in the transmission sector increases to provide transmission of power in a safe manner. But owing to the load growth, the transmission line power flow reaches beyond thermal limit which results in transmission congestion. The congestion management in the present work has been done in a multi-objective framework considering generator rescheduling method as one of the objectives. A Multi-objective Grasshopper Optimization Algorithm (MOGOA) is implemented to perform the optimization for elimination of congested line and minimizing the operational cost of the system. The efficacy of the proposed method has been compared and analyzed with different multi-objective algorithms in IEEE 30 bus test system.
Keywords: Congestion management; generator rescheduling; optimization; multi-objective grasshopper optimization algorithm (MOGOA)